Perancangan Aplikasi Konversi Besaran Berbasis Matlab Untuk Mahasiswa Informatika - Alhidayatuddiniyah Alhidayatuddiniyah; Siwi Puji Astuti; Santy Handayani (UNIVERSITAS INDRAPRASTA PGRI, 2020)
Magnitude is a basic science of physics that is often found in everyday life. Basically, the quantity is divided into two, namely the principal amount and the amount of the derivative. These quantities have their respective sizes, where the size of a quantity can be converted. To help simplify the calculation and introduction of conversion systems, an application for the conversion of principal and derivative quantities using Matlab is designed. Besides being easy to use, this application can be an alternative learning medium in combining Physics with programming, as well as a GUI designed to help conversion calculations.